2021
DOI: 10.12688/f1000research.51613.2
|View full text |Cite
|
Sign up to set email alerts
|

A draft reference assembly of the Psilocybe cubensis genome

Abstract: We describe the use of high-fidelity single molecule sequencing to assemble the genome of the psychoactive Psilocybe cubensis mushroom. The genome is 46.6Mb, 46% GC, and in 32 contigs with an N50 of 3.3Mb. The BUSCO completeness scores are 97.6% with 1.2% duplicates. The Psilocybin synthesis cluster exists in a single 3.2Mb contig. The dataset is available from NCBI BioProject with accessions PRJNA687911 and PRJNA700437.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Psilocybin gene cluster detection was performed using the Augustus version 3.4.0 gene prediction software ( 91 ) with the flags –singlestrand=true to predict genes independently on each strand with the coprinus_cinereus training set. Following gene prediction, the most likely psilocybin BGC for each species was chosen as follows: Using the protein sequences for PsiD (tryptophan decarboxylase), PsiK (kinase), PsiM (methyltransferase), and PsiH (P450) based on the publicly available chromosomal level assembly for P. cubensis ( 92 ), we used BLASTP with default parameters to search for homologs in the predicted translated proteins for each species. The top three hits for each gene were then used together to find putative clusters by examining the gene numbers assigned by augustus.…”
Section: Methodsmentioning
confidence: 99%
“…Psilocybin gene cluster detection was performed using the Augustus version 3.4.0 gene prediction software ( 91 ) with the flags –singlestrand=true to predict genes independently on each strand with the coprinus_cinereus training set. Following gene prediction, the most likely psilocybin BGC for each species was chosen as follows: Using the protein sequences for PsiD (tryptophan decarboxylase), PsiK (kinase), PsiM (methyltransferase), and PsiH (P450) based on the publicly available chromosomal level assembly for P. cubensis ( 92 ), we used BLASTP with default parameters to search for homologs in the predicted translated proteins for each species. The top three hits for each gene were then used together to find putative clusters by examining the gene numbers assigned by augustus.…”
Section: Methodsmentioning
confidence: 99%
“…Psilocybin gene cluster detection was performed using the Augustus version 3.4.0 gene prediction software (Stanke et al 2006) with the flags -singlestrand=true to predict genes independently on each strand, and using the coprinus_cinereus training set. Following gene prediction, the most likely psilocybin BGC for each species was chosen as follows: using the protein sequences for PsiD, PsiK, PsiH, and PsiM based on the publicly available chromosomal level assembly for P. cubensis (McKernan et al 2021), we used BLASTP with default parameters to search for homologs in the predicted translated proteins for each species. The top three hits for each gene were then used together to find putative clusters by examining the gene numbers assigned by Augustus.…”
Section: Gene Prediction Of Psilocybin Gene Cluster and Construction ...mentioning
confidence: 99%
“…Phylogenetic analysis indicated that this cluster has been horizontally acquired by psilocybin-producing mushrooms in other genera with common ecological niches (Awan et al 2018; Reynolds et al 2018), although the direction and relative timing of these transfers remains unclear. Notably, only a select few species of Psilocybe have been investigated at a genomic scale (Fricke et al 2017; Awan et al 2018; Reynolds et al 2018; McKernan et al 2021; Dörner et al 2022), which does not represent all of the known ecologies, and they do not span the phylogenetic range of the two major clades identified by Ramírez-Cruz et al (2013a), severely limiting inferences of evolutionary patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyze the difference between liquid culture and grain spawn substrate for mycelial colonization. Although the genome of P. cubensis has recently been drafted, with 32 contigs mapping 97.6% of the genome by benchmarking universal single-copy orthologs (BUSCO) completeness score ( McKernan et al., 2021 ), to date, no metabolomic mapping of Psilocybe spp. growth stages has been published.…”
Section: Introductionmentioning
confidence: 99%